The Effect of Foreign Direct Investment, Human Development and Macroeconomic Condition on Economic Growth: Evidence from Indonesia - M. Rismawan Ridha; Novia Budi Parwanto (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2020)
The national economic growth that is quite high is not necessarily detached from the existence of important issues such as limited accumulation of national saving capital, domestic needs that are still highly dependent on imported goods, weak of export that rely on primary commodities, insufficient infrastructure development, and low quality of human resources that must be addressed by the Indonesian government. This study aims to analyze the effect of Foreign Direct Investment (FDI), as an alternative source of development funds, the Human Development Index (HDI) as a proxy for the quality of human resources, and Macroeconomic condition represent by Trade Balance (NX), a dummy of Economic Crisis and Gross Fixed Capital Formation (GFCF) on Economic Growth in Indonesia. The data used is time-series data from the period of 1985-2015 sourced from Statistics Indonesia and the World Bank. The analysis technique used in this research is the Error Correction Model (ECM). The results obtained can be made in the following conclusions: 1) Foreign Direct Investment and Trade Balance have a negative and significant impact on Indonesia's long term economic growth, but in the short term, they do not have any significant impact. 2) Human Development and Gross Fixed Capital Formation have a positive and significant impact on Indonesia's economic growth both in the long term and short term. 3) Economic Crisis has a negative and significant impact both in the long term and short term.